The Enviromental Crisis of the Capitalist System from the Perspectives of Thought Economic Heterodox Ecological (Revista Rupturas, 2025)
The objective of this article is to synthesize the main contributions of ecological economics and ecological Marxism, as aspects of heterodox ecological economic thought, emphasizing how they conceptualize the relationship between man and nature and the current environmental crisis. The link between environmental crisis and economic crisis is not circumstantial, both develop with the emergence of capital and capitalist production. This situation has been aggravated by the liberalization and deregulation of capital (globalization). The approach to the linkages between economy and environment is diffuse, and it is not by making a simple practical abstraction of their main systemic synergies, that such diversity should be addressed, today more holistic and comprehensive analyses are required, which go beyond environmental economics.
Keywords: Ecological economics; ecological Marxism; environmental economics; heterodox economics; Sustainable development